2012
DOI: 10.1029/2012ja017983
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and spectral characteristics of energetic electrons in Mercury's magnetosphere

Abstract: [1] The Energetic Particle Spectrometer (EPS) on the MESSENGER spacecraft, in orbit about Mercury since March 2011, has detected bursts of low-and moderate-energy (tens to hundreds of keV) electrons during portions of most orbits. There have been periods when such bursts were observed regularly on every orbit over a span of several weeks, and other periods when electrons were not observed for several days at a time. We have systematically characterized these energetic events on the basis of particle intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 30 publications
3
40
0
Order By: Relevance
“…In surveying the electrons, Ho et al [] observed enhancements of particles within a radial distance of 1.5 R M from the planet. On the nightside near midnight, the electrons are observed near the magnetic equator, while on the dayside they are observed off‐equator at higher latitudes and sometimes even on open field lines in the cusp [ Ho et al , ]. In the dawn and dusk sectors, a small enhancement is observed near the equator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In surveying the electrons, Ho et al [] observed enhancements of particles within a radial distance of 1.5 R M from the planet. On the nightside near midnight, the electrons are observed near the magnetic equator, while on the dayside they are observed off‐equator at higher latitudes and sometimes even on open field lines in the cusp [ Ho et al , ]. In the dawn and dusk sectors, a small enhancement is observed near the equator.…”
Section: Discussionmentioning
confidence: 99%
“…These enhancements however are of lower intensity than the ones observed in the noon or midnight sector. When pitch angle distributions were obtainable within the magnetosphere, they were peaked near 90 ° [ Ho et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…Electrons within the 200-680 eV energy range were already detected by Mariner 10 and interpreted as coming from a hot plasma sheet (Ogilvie & Desch 1977). Furthermore, bursts of low-and moderate energy electrons (tens to hundreds of keVs, Ho et al 2012) have been often recorded by the MESSENGER Energetic Particle Spectrometer (EPS) and X-Ray Spectrometer (XRS). A systematic monitoring permitted to map the burst occurrence.…”
Section: Space Weather At Mercurymentioning
confidence: 99%
“…This issue was not resolved until shortly after the insertion of the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) spacecraft into its Mercury orbit, when data from the energetic particle spectrometer (EPS) demonstrated that the primary energetic particles within Mercury's magnetosphere are electrons and not protons (Ho, Krimigis, et al, 2011; Ho, Starr, et al, 2011). In a subsequent study, Ho et al (2012) reported the spatial distribution of 51 energetic electron (EE) events based on the observations from a full year of MESSENGER's primary orbital mission phase. They found that most of the intense, moderate‐energy (tens to hundreds of keV) electron events occured either at local midnight or at high northern latitudes.…”
Section: Introductionmentioning
confidence: 99%